2019
DOI: 10.1002/fld.4705
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the stability of the least square finite difference scheme and its shock capturing ability in inviscid flows

Abstract: Summary A meshless method – The Least Square Finite Difference scheme (LSFD) with diffusion is analyzed and applied to inviscid flows. The scheme is made second‐order by using a modified difference in the formulation of LSFD. Several numerical experiments, namely the Sod shock tube and the shallow water problems, are carried out and, in the limelight of the results obtained, the ability of the scheme to resolve shock wave, rarefaction wave, and contact discontinuity is discussed. The conditional stability of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 37 publications
(55 reference statements)
0
5
0
Order By: Relevance
“…In Katz, 41 the selection of a proper domain of influence is done using weighting functions. To guarantee the reciprocity of nodes, weights are used in each local connectivity such that certain constraints are satisfied and in Mungur et al 16 the existence of an optimum weight guaranteeing such reciprocity is shown analytically. Oñate et al 42 and Oñate and Idelsohn 43 developed a method that incorporated different least squares weighting methods to improve the accuracy of derivatives and formulations for higher order methods.…”
Section: The Lsfd Schemementioning
confidence: 99%
See 4 more Smart Citations
“…In Katz, 41 the selection of a proper domain of influence is done using weighting functions. To guarantee the reciprocity of nodes, weights are used in each local connectivity such that certain constraints are satisfied and in Mungur et al 16 the existence of an optimum weight guaranteeing such reciprocity is shown analytically. Oñate et al 42 and Oñate and Idelsohn 43 developed a method that incorporated different least squares weighting methods to improve the accuracy of derivatives and formulations for higher order methods.…”
Section: The Lsfd Schemementioning
confidence: 99%
“…If a > 0, D − i is chosen while when a < 0, D + i is chosen in Equation (5). In Mungur et al, 16 a detailed stability analysis is conducted for the first order LSFD scheme. A bounded l ∞ norm for the first order LSFD scheme is obtained using a conditional timestep given by 1 2…”
Section: The Lsfd Schemementioning
confidence: 99%
See 3 more Smart Citations